Molecularly imprinted nanoparticles with recognition properties towards diphtheria toxin for ELISA applications - KAHRAMAN, MEMET VEZİR (My University, 2022)
Plastic antibodies can be used for in vitro neutralization of biomacromolecules with different fragments due to their potential in separation, purification, chemical sensor, catalysis and drug production studies. These polymer nanoparticles with binding affinity and selectivity comparable to natural antibodies were prepared using functional monomer synthesis and copolymerization of acrylic monomers via miniemulsion polymerization. As a result, the in vitro cytotoxic effect from diphtheria toxin was reduced by MIPs. In vitro imaging experiments of polymer nanoparticles (plastic antibodies) were performed to examine the interaction of diphtheria toxin with actin filaments, and MIPs inhibited diphtheria toxin damage on actin filaments. The enzyme-linked immunosorbent assay (ELISA) was performed with plastic antibodies labeled with biotin, and it was determined that plastic antibodies could also be used for diagnostic purposes. We report that molecularly imprinted polymers (MIPs), which are biocompatible polymer nanoparticles, can capture and reduce the effect of diphtheria toxic and its fragment A. HIGHLIGHTS Macromolecules can be imprinted by using their fragments as template molecules. MIPs gain an affinity for the template molecule by covalent binding, non-covalent interactions or ligand interactions, as well as the ability to bind, release and recognize the template molecule.
Keywords: Sağlık Bilimleri; Temel Bilimler; Health Sciences; Natural Sciences; Klinik Tıp (MED); Temel Bilimler (SCI); Doğa Bilimleri Genel; ÇOK DİSİPLİNLİ BİLİMLER; Clinical Medicine (MED); Natural Sciences (SCI); NATURAL SCIENCES, GENERAL; MULTIDISCIPLINARY SCIENCES; Multidisipliner; Multidisciplinary; Molecularly imprinted polymer; plastic antibody; diphtheria toxin; ELISA